Study of Mathematical Modeling for Plant Disease Transmission: A Systematic Literature Review during 2012-2022 - Tresna, Sanubari Tansah; Anggriani, Nursanti; Supriatna, Asep Kuswandi (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
Many models representing disease transmission have been constructed and analyzed mathematically. However, literature studies on the mathematical models for vector-borne disease are sparse, especially on the plant disease transmission model. This study aims to obtain information about the research conducted and find room for developing the model, including mathematical analysis, intervention used, and biological factors considered. We employ a Systematic Literature Review (SLR) to explore all of the studies on plant disease transmission modeling collected from four digital databases. First, the JabRef reference manager helps conduct the inclusion and exclusion processing. Then, we obtain 60 selected articles that passed the criterion. Next, the VOSviewer application is resulting a bibliometric analysis of the database containing chosen articles. Finally, we classify the model constructed based on the system used and elaborate on the intervention used. The results show that the existing researcher clusters are not linked to each other, and the models only consider usual interventions such as roguing and insecticide spraying. Hence, there is much room to build collaboration between the researcher and develop models for plant disease transmission by considering the other various intervention and biological factors in the model to improve further.